Problematika Kewenangan Administrasi Kependudukan Sesuai Peraturan Pemerintah Nomor 40 Tahun 2019 - Ashara Putra Mansien (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2020)
This study seeks to understand the external constraints that arise in the implementation of population administration authority that stems from the tightness of ministerial regulations on regions and the division of authority between the central and regional governments. This paper aims to analyze potential obstacles in the implementation of population administration affairs according to Government Regulation Number 40/2019. The research method uses a literature study, where the authors collect data systematically and make a synthesis. First, there is a distortion in the implementation of the principles of regional governance where there is a conflict between central and regional regulations, central regulations tend to be centralized and this affects the unbalanced budget composition, making it difficult for regions to work optimally. Second, the distribution of population administrative affairs and the criteria for assigning functions. Where the ministry gives orders that are not written in PP 40/2019 and work on things that have been done in the regions. Then the weak distribution of monitoring and coordination functions in the implementation of activities causes conflicts between provinces and districts/cities. In conclusion, the implementation of PP. 40 of 2019 raises obstacles in the relation of authority, institution, finance, and supervision of the central and regional governments. The solution offered is to improve communication and coordination patterns and the central government immediately to establish representative offices in provinces, districts/cities, and villages that specifically work on deconcentration/assistance tasks.